Cutting the line in wireline with an Autonomous Sonde - Kepic, Anton; Podolska, A.; Greenwood, A.; Dupuis, C.; Stewart, G. (2015)
Rock core has long been one of the pillars of mineral exploration strategy. This strategy, however, is becoming less viable as the depth of exploration targets continue to increase. Exploration strategies based on physical and chemical attributes of the rock-mass measured in-situ have the best chances to deliver efficient exploration programs by providing new data channels that can be used to improve the models of the deposits. Unfortunately, the logistic costs of acquiring these data using conventional wire-line methods have precluded their widespread use in the mineral industry. The autonomous sonde concept presented in this work drastically reduces the logistics costs of acquiring in-situ measurements. The autonomous sonde has been developed to integrate fully with the normal operations of current drill rigs. As such, it requires no specialised operator or equipment and no rig modifications. In this work, we present the results of field trials of the autonomous sondes at two Australian field sites. In the first experiment, we show that a pressure transducer can be used to evaluate the position of the sonde and to depth register the natural gamma data. In the second experiment, we show data acquired when the autonomous sonde protrudes through the bottom of the drill string and is brought back to surface by pulling up the rods. The results show a good repeatability between logging runs and data quality compares favourably to traditional wireline data.